2010
DOI: 10.4491/eer.2010.15.4.225
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Combined Microwave and Thermal Desorption Process for Contaminated Soil

Abstract: In order to treat soil contaminated with high percentages of water and petroleum, the combined microwave and thermal desorption process was studied, which was composed of the consecutive connection of two pre-treatment processes. For the thickness of the contaminated soil layer on the transfer conveyor belt, the optimal total petroleum hydrocarbon (TPH) removal rate was studied with respect to the duration of microwave exposure in the consecutive process combined with thermal desorption. The TPH removal rate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…One previous study reported 94.7% of TPH removal after 15 min thermal desorption of petroleum oil-contaminated soil (initial concentration of 5133 ± 508 mg kg −1 ) at 200 °C in a rotary kiln [20]. In another study, the maximum TPH removal efficiency of about 98% was achieved at 500 °C after 15 min treatment of the combined microwave and thermal desorption processes [21].…”
Section: Removal Of Tph and Ucmmentioning
confidence: 95%
“…One previous study reported 94.7% of TPH removal after 15 min thermal desorption of petroleum oil-contaminated soil (initial concentration of 5133 ± 508 mg kg −1 ) at 200 °C in a rotary kiln [20]. In another study, the maximum TPH removal efficiency of about 98% was achieved at 500 °C after 15 min treatment of the combined microwave and thermal desorption processes [21].…”
Section: Removal Of Tph and Ucmmentioning
confidence: 95%
“…97 Microwave energy has also been reported for rapid recovery of crude oil from soil. 97 Microwave energy has also been reported for rapid recovery of crude oil from soil.…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…The energy efficiency and therefore economic performance of thermal desorption especially in wet soils may be improved by pre-treatment using microwave heating to remove moisture and a proportion of petroleum contamination. 97 Microwave energy has also been reported for rapid recovery of crude oil from soil. It was recently reported 98 that microwave heating enhanced by carbon ber added as a microwave absorber was able to recover 94% of crude oil contaminants.…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…For a full-scale application of MW remediation, a schematic design of a microwave heating system has recently been reported by Ha and Choi (2010), Barba et al (2011) or Chien (2012.…”
Section: Introductionmentioning
confidence: 99%